Novel rare genetic variants of familial and sporadic pulmonary atresia identified by whole-exome sequencing - Xing Junyue; Wang Hongdan; Xie Yuanyuan; Fan Taibing; Cui Cunying; Li Yanan; Wang Shuai; Gu Weiyue; Wang Chengzeng; Tang Hao; Liu Lin (Open Life Sciences, 2023)
Pulmonary atresia (PA) is a severe cyanotic congenital heart disease. Although some genetic mutations have been described to be associated with PA, the knowledge of pathogenesis is insufficient. The aim of this research was to use whole-exome sequencing (WES) to determine novel rare genetic variants in PA patients. We performed WES in 33 patients (27 patient–parent trios and 6 single probands) and 300 healthy control individuals. By applying an enhanced analytical framework to incorporate de novo and case–control rare variation, we identified 176 risk genes (100 de novo variants and 87 rare variants). Protein‒protein interaction (PPI) analysis and Genotype-Tissue Expression analysis revealed that 35 putative candidate genes had PPIs with known PA genes with high expression in the human heart. Expression quantitative trait loci analysis revealed that 27 genes that were identified as novel PA genes that could be affected by the surrounding single nucleotide polymorphism were screened. Furthermore, we screened rare damaging variants with a threshold of minor allele frequency at 0.5% in the ExAC_EAS and GnomAD_exome_EAS databases, and the deleteriousness was predicted by bioinformatics tools. For the first time, 18 rare variants in 11 new candidate genes have been identified that may play a role in the pathogenesis of PA. Our research provides new insights into the pathogenesis of PA and helps to identify the critical genes for PA.